2022
DOI: 10.3390/plants11192664
|View full text |Cite
|
Sign up to set email alerts
|

Pea Breeding for Resistance to Rhizospheric Pathogens

Abstract: Pea (Pisum sativum L.) is a grain legume widely cultivated in temperate climates. It is important in the race for food security owing to its multipurpose low-input requirement and environmental promoting traits. Pea is key in nitrogen fixation, biodiversity preservation, and nutritional functions as food and feed. Unfortunately, like most crops, pea production is constrained by several pests and diseases, of which rhizosphere disease dwellers are the most critical due to their long-term persistence in the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 284 publications
(462 reference statements)
0
9
0
Order By: Relevance
“…The heredity of microbiomes and their connection to agronomic traits are both supported by recent studies. Studies conducted on different genotypes of canola showed that there was a notable difference in the percentage of microbial species [ 134 , 135 ]. As there is growing evidence that the microbiome affects host performance, breeding programs must successfully integrate genotype, environment, microbiome, and management interactions [ 136 ].…”
Section: Translation Of Knowledge To Field Applicationmentioning
confidence: 99%
“…The heredity of microbiomes and their connection to agronomic traits are both supported by recent studies. Studies conducted on different genotypes of canola showed that there was a notable difference in the percentage of microbial species [ 134 , 135 ]. As there is growing evidence that the microbiome affects host performance, breeding programs must successfully integrate genotype, environment, microbiome, and management interactions [ 136 ].…”
Section: Translation Of Knowledge To Field Applicationmentioning
confidence: 99%
“…There are both many different crops and many different pests and diseases that cannot be addressed in this paper. Recent reviews are available covering resistance breeding either by crop (i.e., common bean (Taboada et al, 2022), faba bean (Rubiales and Khazaei, 2022), grasspea (Ellis et al, 2022), mungbean (Nair et al, 2019), lentil (Roy et al, 2023), pea (Parihar et al, 2022), soybean (Lin et al, 2022)), or by groups of diseases or pests (i.e., insect pests (Edwards and Singh, 2006; Keneni et al, 2011); airborne biotrophic pathogens (Sillero et al, 2006; Martins et al, 2020), necrotrophic pathogens (Tivoli et al, 2006; Bilkiss et al, 2019), soil pathogens (Wohor et al, 2022), parasitic weeds (Rubiales et al, 2006; Rubiales, 2018), nematodes (Ruanpanun and Somta, 2021) or viral diseases (Jha et al, 2023) among others). Attention is needed to better understand not only the genetic basis of resistance, but also the biology of the pathogens, and monitoring their distribution.…”
Section: Breeding Objectives To Better Meet Agroecological Requirementsmentioning
confidence: 99%
“…Breeding for resistance proved to be a valuable strategy to cope with Oc and other parasitic weeds belonging to the botanic family of Orobanchaceae ( Jamil et al., 2011 ; Fernández-Aparicio et al., 2014 ; Jamil et al., 2021 ; Li et al., 2023a ), whereas agronomic and chemical control methods displayed limited efficacy ( Fernández-Aparicio et al., 2016a ). However, no Oc-resistant pea cultivar is commercially available ( Rubiales, 2014 ; Wohor et al., 2022 ); thus, pea cultivation has been abandoned in several areas with a large Oc seed bank ( Renna et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%